2022
DOI: 10.3390/economies10070155
|View full text |Cite
|
Sign up to set email alerts
|

Do Village Allocation Funds Contribute towards Alleviating Hunger among the Local Community (SDG#2)? An Insight from Indonesia

Abstract: Using an exclusive data set from Indonesia in 2018–2020, this study aims to prove whether there is a relationship between the allocation of village funds and the level of hunger in the community. In particular, this study tries to find out whether the Village Fund allocation policy has an effect on the achievement of the United Nations Sustainable Development Goal 2 (SDG#2). Using a quantitative method with regression analysis, this study found that the allocation of village funds by the Indonesian government … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The quantitative method with a verification approach. Manurung et al [21] To examine the positive correlation between rural economic development, the accuracy of village government decision-making, and the ecological environment of rural habitats in sustaining rural habitats.…”
Section: Hartojo Et Al [14]mentioning
confidence: 99%
See 3 more Smart Citations
“…The quantitative method with a verification approach. Manurung et al [21] To examine the positive correlation between rural economic development, the accuracy of village government decision-making, and the ecological environment of rural habitats in sustaining rural habitats.…”
Section: Hartojo Et Al [14]mentioning
confidence: 99%
“…Implementing VF transfer improved rural economic growth in underdeveloped villages, as studies [12,14] reported. VF programs also supported hunger and poverty alleviation in all areas of Indonesia's villages [21].…”
Section: Indonesiamentioning
confidence: 99%
See 2 more Smart Citations
“…This is the basis for conducting this research to examine how the village fund program policies are implemented to overcome the problems of rural communities in Wajo District. This is also based on the study of Manurung et al (2022), which found that village funds allocated to villages in Indonesia have effectively alleviated poverty in rural communities.…”
Section: Introductionmentioning
confidence: 99%